Epistaxis at Patan Hospital: A Retrospective Review and an Audit - Dangol, Bhawana; Shrestha, Namita; Yadav, Deepak; Devkota, Ishwor R; Nepal, Ajit; Bhandari, Sangita (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: The  objective  of  this  study was to review the cases of epistaxis and audit its management at Patan Hospital. Materials and Methods: This was a retrospective study and an audit carried out in patients admitted for epistaxis in Patan Hospital from August 2012 to August 2014. All the patients with primary epistaxis were included. The data were analyzed in terms of the specific defined parameters and were compared with that of Guy’s Hospital, United Kingdom, of year 2011.Results: Out of 146 patients, 111 had primary epistaxis. Ninety-three patients (83.78%) with primary epistaxis had anterior bleeding and 18 patients (16.21%) had posterior bleeding. The majority of the patients (31.53%) were treated with chemical cautery, followed by anterior nasal packing (27.02%). Eleven patients (10%) underwent sphenopalatine artery cauterization. The data of our hospital were optimal or near optimal in some aspects like documented initial nasal examination, and initial cautery attempt whereas, parameters like re-bleeding rate, surgical intervention and endoscopic nasal examination after cessation of bleeding were found to be sub-optimal.Conclusion: The improvements are required in some aspects of management of epistaxis like decreasing the re-bleeding rate, increasing the timely surgical intervention and compulsory endoscopic evaluation of nasal cavity after cessation of bleeding. This can be attained with adherence to the protocol as proposed. A multi-center audit would be required to develop a common consensus regarding its management.Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, Page: 26-30